AB0964 THE ASSOCIATION BETWEEN RESIDUAL SYMPTOMS AND CERVICAL SPINE LESIONS IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Kashiwagura, T.; Kobayashi, M.; Sugimura, Y.; Kawano, T.; Sato, H.; Miyakoshi, N.; Shimada, Y.
Abstract : Background: Treatment outcomes in rheumatoid arthritis (RA) have been improved with advances in drug therapy. In daily clinical practice, the outcomes are assessed based on the presence of swollen or tender joints, global assessment using a visual analog scale by a patient (GVAS) and a physician (DrVAS), etc., in addition to inflammatory findings. Although inflammation and joint symptoms are suppressed, many patients show no improvement in GVAS scores. The reported residual RA symptoms include morning stiffness (MS), pain (P), and dullness (D), but their causes are not completely known. Latent cervical spine lesions sometimes exist in RA, but their association with residual RA symptoms is unknown. Objectives: We examined cervical spine lesions and residual symptoms in patients with RA who achieved the therapeutic goal. Methods: Of 124 patients with RA, 82 (25 men and 57 women) who achieved a low disease activity (LDA) state on the Disease Activity Score for 28 joints with erythrocyte sedimentation rate (DAS28-ESR) were included. The mean age was 65.7 (28- 83) years, and the disease stage was Stage I in 28 patients, Stage II in 14, Stage III in 13, and Stage IV in 27. Dysfunction was graded as Class 1 in 63 patients, Class 2 in 18, and Class 3 in one (Steinbrocker classification). Biopharmaceuticals had been administered in 27 patients. As for disease activity, the DAS28-ESR scores indicated complete remission in 54 patients and LDA in 28. The survey form was used to investigate the presence or absence/duration of MS, the presence or absence/severity of P (Pain VAS), and the presence or absence/severity of D (Dullness VAS). On lateral functional radiographs of the cervical spine, patients with spinal lesions were selected and divided into the asymptotic stability (ASS; atlantoaxial dislocation ≥3 mm) + vertical setting (VS; Ranawat value <13 mm) group, the cervical spondylolisthesis group (≥3 mm of slippage on dynamic radiographs), and the spondylolisthesis group (≥3 mm of slippage on dynamic radiographs). They were examined for association with residual symptoms. Results: According to cervical spine lesions, the patients who achieved the therapeutic goal were divided into the ASS+VS group comprising 15 patients (18.3%), the spondylolisthesis group comprising 11 (13.4%), and the stenosis group comprising 18 (22.0%). Among them, only the spondylolisthesis group showed significant differences in residual RA symptoms. In the spondylolisthesis group, the disease duration was longer, but there was no difference in age. MS, P, and D were significantly severer. The duration of MS was longer, and both Pain and Dullness VAS scores were higher. The score on each component of the DAS28 showed no difference in inflammatory findings. GVAS and DrVAS scores were higher. No common perceptions of spinal symptoms were shared between any patients with cervical spine lesions and physicians. Conclusion: Improved patient-reported outcomes (PROs) are considered to be important to achieve more complete remission. There are various reports on the causes of residual RA symptoms, but many aspects remain unknown. Based on the results of this study, because asymptomatic subaxial subluxation is one of concerns in patients with spondylolisthesis with dynamic instability of the cervical spine, cervical spine diseases should also be considered in patients with severe residual symptoms. Not only radiography but also magnetic resonance imaging needs to be performed. Acknowledgments: The authors wish to acknowledge Miss Sasaki Disclosure of Interests: None declared